2021
DOI: 10.1177/15910199211057332
|View full text |Cite
|
Sign up to set email alerts
|

A novel intracranial exchange guidewire improves the navigation of various endovascular devices: An in vitro study of challenging situations

Abstract: Objective Neuroendovascular procedures rely on successful navigation and stable access to the target vessel. The Stabilizer is a 300 cm long exchange wire with a 0.014 diameter and a soft, flexible stent at the distal end designed to assist with navigation and device delivery. This study aims to assess the efficacy of the Stabilizer for navigation in a variety of challenging environments. Methods The efficacy of the Stabilizer was evaluated using three challenging vascular models: a giant aneurysm model, a sev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 34 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…A balloon can be used in a similar fashion to the Stabilizer to prevent accidental movement of the guidewire. However, the Stabilizer has the added advantage of allowing blood flow through the vessel during the exchange [ [8] , [9] , [10] , [11] ]. Traditional stent retrievers have also been used for difficult navigation or exchange maneuvers but because the push wire is not long enough, special precautions are necessary to prevent air embolism [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A balloon can be used in a similar fashion to the Stabilizer to prevent accidental movement of the guidewire. However, the Stabilizer has the added advantage of allowing blood flow through the vessel during the exchange [ [8] , [9] , [10] , [11] ]. Traditional stent retrievers have also been used for difficult navigation or exchange maneuvers but because the push wire is not long enough, special precautions are necessary to prevent air embolism [ 9 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent in vitro study demonstrated significantly greater success with the Stabilizer when navigating challenging settings and performing exchange maneuvers with stiff devices compared to a traditional guidewire [ 11 ]. In this first-in-human experience using the Stabilizer, we were able to successfully navigate the device in all five cases with no clinically significant adverse events.…”
Section: Discussionmentioning
confidence: 99%